CHINESE-INDONESIANS MUST SUPPORT #PAPUANLIVESMATTER - Astin Leuisa Masyafira; Vionny Lydia Puspita; Yesiana Vianingrum (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2020)
As we know that Indonesia has so many groups of people and cultures, because it makesus be one in Pancasila, which has meaning even though we are different but we are still one entity.But without our realizing, there are so many racists that we do by our own siblings, Papuadescents. When there are demonstration about racism in U.S, it perfectly has an impact on thePapuan population as well. So in this time, we will discuss about the â€œPapuansLivesMatterâ€ demoin Indonesia. (1) What provoked the demo aside from the giant wave # BlackLivesMatter UnitedStates? (2) Why do they think racism against Papuans does not deserve special attention? Andthen (3) Why do they say that comparing the racism experienced by African-Americans with thatexperienced by Papuans is ridiculous?